Integration of Local Cultural Visualization in the DACAR Model to Develop Early Childhood Creativity - Gusmaniarti, Gusmaniarti; Shoffa, Shoffan; Wahono, Wahono; May Zahra, Fira (LP. Ma'arif Janggan Magetan, 2025)
This study aims to evaluate the effectiveness of integrating local-wisdom-based visual technology into the DACAR learning model (Description, Analysis, Story, Reflection) to enhance cognitive and creative abilities in early childhood. Conducted at TK ABA 69 Surabaya with 27 children aged 5–6 years, this research employed a descriptive quantitative approach with a one-group pretest–posttest design. Seven indicators of cognitive and creative development were assessed using a 1–3–5 scoring rubric. Data were collected through observation and task-based instruments and analyzed using paired t-tests for normally distributed data or Wilcoxon Matched-Pairs Tests if normality was not met. Descriptive statistics and visualizations complemented the analysis. Results showed that while posttest scores improved across all indicators, only one—children’s ability to ask relevant questions—demonstrated statistically significant improvement (median = 0.5; CI = 0.5–1; p < 0.05). Other indicators, such as curiosity, analysis, connection to prior experience, creative output, imagination, and local culture recognition, showed nonsignificant changes (median = 0–0.5; p > 0.05). These findings indicate that visual technology effectively supports contextual questioning but is insufficient to foster higher-order thinking and creativity within a short intervention period. Contributing factors include prior familiarity with local culture and limited learning duration. This study recommends expanding assessment tools, applying project-based learning, and integrating digital–physical media to better stimulate exploration, critical thinking, and creativity in early childhood education.